Lipoxin (LX)A(4) and Aspirin-triggered 15-epi-LXA(4) Inhibit Tumor Necrosis Factor 1α–initiated Neutrophil Responses and Trafficking: Regulators of a Cytokine–Chemokine Axis - Hachicha, Mohamed (The Rockefeller University Press, 1999)
The impact of  lipoxin A(4) (LXA(4)) and aspirin-triggered lipoxins (ATLs) was investigated in tumor necrosis factor (TNF)-α–initiated neutrophil (polymorphonuclear leukocyte) responses in vitro and in vivo using metabolically stable LX analogues. At concentrations as low as 1–10 nM, the LXA(4) and ATL analogues each inhibited TNF-α–stimulated superoxide anion generation and IL-1β release by human polymorphonuclear leukocytes. These LXA(4)-ATL actions were time and concentration dependent and proved selective for TNF-α, as these responses were not altered with either GM-CSF– or zymosan-stimulated cells. TNF-α–induced IL-1β gene expression was also regulated by both anti-LXA(4) receptor antibodies and LXA(4)-ATL analogues. In murine air pouches, 15R/S-methyl-LXA(4) dramatically inhibited TNF-α–stimulated leukocyte trafficking, as well as the appearance of both macrophage inflammatory peptide 2 and IL-1β, while concomitantly stimulating IL-4 in pouch exudates. Together, these results indicate that both LXA(4) and ATL regulate TNF-α–directed neutrophil actions in vitro and in vivo and stimulate IL-4 in exudates, playing a pivotal role in immune responses.